2010
DOI: 10.1051/0004-6361/201116661
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields generated by r-modes in accreting quark stars

Abstract: We show that the r-mode instability can generate strong toroidal fields in the core of accreting millisecond quark stars by inducing differential rotation. We follow the spin frequency evolution on a long time-scale, taking into account the magnetic damping rate in the evolution equations of r-modes. The maximum spin frequency of the star is only marginally lower than without the magnetic field. The late-time evolution of the stars that enter the r-mode instability region is instead quite different if the gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…In this type of stars the viscosity and thus the r-mode instability window is quite different from that of normal NSs [32]. Moreover, the evolution of the internal magnetic fields and the magnetic properties of the compact star are also expected to be different [8,33].…”
Section: The Overall Evolutionary Sequence: a General Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this type of stars the viscosity and thus the r-mode instability window is quite different from that of normal NSs [32]. Moreover, the evolution of the internal magnetic fields and the magnetic properties of the compact star are also expected to be different [8,33].…”
Section: The Overall Evolutionary Sequence: a General Discussionmentioning
confidence: 91%
“…[1][2][3]6] and in the case of accreting millisecond neutron and quark stars in Refs. [7,8]. Magnetic fields deform the star and if the magnetic axis is not aligned with the rotation axis the NS undergoes free body precession.…”
Section: Introductionmentioning
confidence: 99%
“…We have discussed the evolution of the external magnetic field of recycled MSPs due to the diffusion of strong internal magnetic fields generated by r-modes during the mass accretion phase. Our analysis is based on the previous work of Cuofano & Drago (2010) and Bonanno et al (2011) where it has been shown that r-modes generate strong internal magnetic fields in accreting compact stars. We have shown that the growth of the external magnetic field affects the evolution of the spin-down rate Ṗ of the MSPs and that this mechanism can explain the high Ṗ of J1823-3021A and of J1824-2452A.…”
Section: Discussionmentioning
confidence: 99%
“…In recent papers it has been proposed a mechanism based on the r-mode instability for the evolution of the internal magnetic field in millisecond accreting compact stars (Cuofano & Drago 2010;Bonanno et al 2011;Cuofano et al 2012). R-modes represent a class of oscillation modes in rotating neutron stars, which are unstable with respect to the emission of gravitational waves (Andersson & Kokkotas 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ho & Lai 2000). More recently, Cuofano & Drago (2010) and Bonanno et al (2011) investigated the role of magnetic field generation by the unstable r ‐mode, showing that a very strong toroidal magnetic field can be generated, which can, in turn, modify the instability.…”
Section: Introductionmentioning
confidence: 99%